Throughput analysis of CDMA systems using multiuser receivers. - Qingchong Liu
Throughput bounds are attained for random channel access multichannel code-division multiple-access (CDMA) systems and spread slotted Aloha systems employing multiuser receivers. It is shown that the normalized throughput of these two systems reaches 1.0 exponentially fast in the region r/K<1, where, r is the average number of simultaneous users in each channel in the random channel access multichannel CDMA system and the packet arrival rate in the spread slotted Aloha system, respectively, and K is the maximum number of users which the multiuser receiver can handle at the same time. Therefore, both of the random channel access multichannel CDMA system and the spread slotted Aloha system employing multiuser receivers can achieve perfect throughput while being stable in the region r/K=1-δ, δ>0. The maximum throughput of the random channel access multichannel CDMA systems is found as K-√(1-(1/M))KlogK-O(logK), where M is the number of channels in the system. The maximum throughput is reached when the average number of simultaneous users is rm=K-√((1-(1/M))KlogK))+O(√(K/logK)). The maximum throughput of the spread slotted Aloha systems is K-√(KlogK)-O(log K). The maximum throughput is reached when the packet arrival of Poisson distribution has the arrival rate λm=K-√(KlogK)+O(√(K/logK))
Keywords: Poisson distribution; Code-division multiple-access.; Maximum throughput; Mobile communication systems; Mobile radio; Multiuser detection; Multiuser receivers; Normalized throughput; Packet arrival rate; Random channel access multichannel CDMA systems; Spread slotted Aloha system; Spread slotted Aloha systems; Throughput analysis; Throughput bounds